Síntese e estudo das propriedades luminescentes de cristais LaAlO3:C para aplicação em dosimetria da radiação ultravioleta - Neriene Alves (2018)
In this work it was performed the synthesis of undoped and 0,1 wt.% carbon-doped polycrystalline lanthanum aluminate (LaAlO3). Their thermoluminescent properties were investigated for application in ultraviolet radiation dosimetry. That material present a perovskite structure, which has been widely investigated because its crystalline structure favors the formation of anionic defects and enables a variety of elements to be accommodated in the crystalline lattice; these factors are directly related to the luminescence materials. The main steps of the work were: the characterization of the thermoluminescent sensitivity of powders obtained by different mixtures of Al2O3, La2O3 and carbono. X Rays diffraction, Ultraviolet and Visible Spectroscopy, Fourier Transform Infrared Spectroscopy and Scanning Electron Microscopy were performed. The powder was synthesized by the solid state reaction method by successive processes of grinding and heat treatment at 1700°C, in hydrogen atmosphere. The formation of the LaAlO3 phase was characterized by X-ray diffraction, but the presence of La(OH)3 was also observed and associated with the increase of the thermoluminescent sensitivity. We found that all the analyzed mixtures, including pure lanthanum aluminate, showed great sensitivity to Ultraviolet Radiation (radiação UV). However the group of samples in which the carbon was added to the lanthanum oxide presented better linearity and reproducibility in the tests performed. The kinetic parameters of the thermoluminescent curves were obtained by the peak shape method. The efficiency of optical blanking for individuals thermoluminescent peaks was evaluated and demonstrated good results. Images of the thermoluminescent emission obtained by meansure of films of the samples presented promissing results regarding the sensitivity and resolution for the ultraviolet radiation. The film should be able to represent information on the dose distribution and/or homogeneity of a field of UV radiation from artificial sources, such as the lamps used in phototherapy procedures.